RELATIONSHIP BETWEEN FAST FOOD CONSUMPTION, PHYSICAL ACTIVITY WITH THE INCIDENCE OF OVERWEIGHT AND OBESITY IN STAI LA TANSA MASHIRO STUDENTS - Tata Sudita; Anis Ervina; Nabilla Fawwaz Siwi Wardoyo (Consilium Sanitatis: Journal of Health Science and Policy, 2024)
Objective: This study aims to analyze the relationship between fast food consumption, physical activity, and the incidence of overweight and obesity among STAI La Tansa Mashiro students. Obesity is an increasing global health problem, especially among university students. Methods: The research method used was a quantitative survey with random sampling. Data were collected through a questionnaire that measured the frequency of fast food consumption and physical activity levels. Results: The results showed that there was no significant relationship between fast food consumption and the incidence of overweight and obesity, and low physical activity was at risk for this problem. Conclusion: The findings are expected to form the basis for better health interventions among university students. .